Entrepreneurship Education in Higher Education - Fahmi Idris Idris (IJHCM (International Journal of Human Capital Management), 2018)
Unemployment, economic growth, and low entrepreneurial ratio hasbecome current problem in Indonesia. Entrepreneurship education is animportant form of intervention to overcome these problems.This articlereviews the concepts and developments in the field of entrepreneurshipeducation in the literature.Furthermore, this study critically examines thedevelopment of entrepreneurship education in Indonesia and implementthe existing theoretical framework to recommend a number ofimprovements that can be taken by higher education and otherstakeholders to enhance the quality of entrepreneurship education inIndonesia.